2016
DOI: 10.1016/j.bpj.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Orai1 Concatemers Supports a Hexameric Stoichiometry for the CRAC Channel

Abstract: Store-operated Ca entry occurs through the binding of the endoplasmic reticulum (ER) Ca sensor STIM1 to Orai1, the pore-forming subunit of the Ca release-activated Ca (CRAC) channel. Although the essential steps leading to channel opening have been described, fundamental questions remain, including the functional stoichiometry of the CRAC channel. The crystal structure of Drosophila Orai indicates a hexameric stoichiometry, while studies of linked Orai1 concatemers and single-molecule photobleaching suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 51 publications
(84 reference statements)
5
80
0
Order By: Relevance
“…Thus, function of the concatemeric hexamer is sensitive to replacement of each of the six residues with the pore-dead E106A mutation indicating that all the residues are required for channel function. Interestingly, the function of the other shorter concatemers (pentamers, tetramers, trimers, and dimers) resulted from the first two N-terminal subunits being unexpectedly fed into a hexameric structure composed of a “trimer of dimers.” Our results strongly suggested that the functional Orai1 channel is indeed a hexamer (Cai et al 2016) agreeing with other studies published at the same time (Yen et al 2016)…”
Section: 3 Structure and Function Of The Orai Channelsupporting
confidence: 93%
“…Thus, function of the concatemeric hexamer is sensitive to replacement of each of the six residues with the pore-dead E106A mutation indicating that all the residues are required for channel function. Interestingly, the function of the other shorter concatemers (pentamers, tetramers, trimers, and dimers) resulted from the first two N-terminal subunits being unexpectedly fed into a hexameric structure composed of a “trimer of dimers.” Our results strongly suggested that the functional Orai1 channel is indeed a hexamer (Cai et al 2016) agreeing with other studies published at the same time (Yen et al 2016)…”
Section: 3 Structure and Function Of The Orai Channelsupporting
confidence: 93%
“…The conclusion from the crystal structure that Orai is a hexamer was reinforced by determination of the molecular mass of the purified channel complex using light scattering/UV absorbance/refractive index measurements and by protein cross-linking of Drosophila Orai expressed in mammalian HEK293 cell membranes that produced a clearly resolvable ladder of multimers up to the hexamer (Hou et al 2012). Two careful new studies examining Orai1 concatemers explain the earlier concatemer results and support a hexameric structure (Yen et al 2016; Cai et al 2016). …”
Section: 5 Channel Architecturementioning
confidence: 71%
“…Consistently, atomic force microscopy revealed that human Orai1 assembles as a hexamer and STIM1 binds to Orai1 hexamer with six-fold symmetry [84]. A recent study using Orai1 concatemers further supported a hexameric stoichiometry for the SOC channel [85]. It has been postulated that Orai1 diffuses passively into ER-PM junctions, and is then trapped and activated by prior translocated STIM1 to elicit SOCE.…”
Section: Important Roles Of Er-pm Junctions In Ca2+ Signalingmentioning
confidence: 91%